Analisis Kinerja Pegawai Dalam Pelayanan Administrasi Kependudukan - Debyla Salshalina Ardil; Isna Fitria Agustina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the performance of employees in the Civil Registration Administration Service in the Village of Kajeksan, Tulangan District, Sidoarjo Regency. Employee performance in civil registration administration is essential for community needs related to population data. The lack of human resource skills poses challenges for employees in providing effective and efficient services, leading to dissatisfaction among individuals dealing with population documents. The research employs a qualitative descriptive research method to examine the conditions of a specific object. The results indicate that; The quality of employee performance is good in utilizing the information technology available, with employees fulfilling their duties and responsibilities; The quantity of employee performance is optimally sufficient, even when handling a large number of documents, despite server constraints; Timeliness of employee performance is reasonably optimal, considering the ability to provide services within a timely manner, although there are server-related challenges; The effectiveness of employee performance ensures the delivery of the best services, facilitated by technological tools; Employee self-reliance is optimal, with individual capabilities aligning with the community's expectations for processing population documents. Keywords - Employee Performance, Population Administration, Service